Analysis of customer satisfaction of regional drinking water company Tirta Mulia Karimun the Riau Islands - Ngaliman, Ngaliman; Rafiza, Raja; Khaddafi, Muammar (Goodwood Publishing, 2024)
Purpose: This study aims to analyze the direct and indirect effects of product quality, volume, tariff, and service on customer satisfaction at PDAM Tirta Mulia Karimun, Riau Islands Province. Research Methodology: This study used a quantitative approach. The sample consisted of 200 respondents, who were analyzed using the SMARTPLS program. After validity and reliability tests were conducted, a hypothesis test was performed. Results: The findings show that product quality, volume, and service have a significant direct effect on customer satisfaction, while tariffs do not have a direct significant effect. However, product quality, volume, and tariffs each significantly affected satisfaction indirectly through service quality (p < 0.05). The overall model explained 70.4% of the variance in customer satisfaction. Conclusions: Customer satisfaction with PDAM Tirta Mulia Karimun is significantly influenced by product quality, volume, and services. Although tariffs do not directly influence satisfaction, they have a significant indirect effect on service. Improvements in water quality and volume are the most critical areas for increasing customer satisfaction. Limitations: This study was limited to customers of PDAM Tirta Mulia Karimun in one regency, which may affect the generalizability of the results to other regions or service providers. Contribution: This study provides empirical evidence of how indirect effects through service quality mediate customer perceptions, which can guide policy and operational improvements in regional water service companies.